IMPLEMENTATION OF REMEDIAL TEACHING IN OVERCOMING STUDENTS' LEARNING DIFFICULTIES IN FIQIH SUBJECTS IN MADRASAH - Yaqin, Muhammad Ainul; Arief Wijaksono, Muhammad Eko (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Education often ignores the values of freedom of thought towards students in the learning process. They are considered as machines that must obey the system. Without giving the opportunity to express expression in learning according to each other's talents, both in terms of action, as well as in expressing ideas. Paulo Freire, educational scientist provides fresh air to students in taking learning that has an interpretation of freedom. This study uses the documentary method. The author collects several book sources, then classifies them based on groups (biography, Paulo Freire's theory and liberation pedagogy in learning). teachers can be understood according to their respective talents. Studying and reading books requires concentration, because according to Paulo Freire's theory, real learning is to re-create, re-create and rewrite. Students must understand what the learning objectives are in each theme, because pedagogy is not some kind of banking system, students are considered empty space. Students are whole human beings who have talents and abilities, so it is the educator's job to discover and develop students' abilities. Not necessarily - students have to remember, memorize and only understand the learning given by the teacher. When this theory is applied to liberate students in a lesson, solving some of the student's problems must be done carefully with an educator's understanding of the concept of education